Esophageal Diverticulum and Megaesophagus in a Dog and a Cat - Oliveira, Thaís Nascimento de Andrade; Veloso, Jéssica Fontes; Rocha, Paula dos Santos; Lacerda, Priscila Dutra; Carlos, Renata Santiago Alberto (Acta Scientiae Veterinariae, 2018)
Background: Esophageal diverticula are pouch-like dilatations in the esophageal wall that rarely affect dogs and cats, and may have the megaesophagus as a base cause. The definitive method of diagnosis is the contrasting chest X-ray that will visualize the sacculation. Cases: Case 1. A feline male, mixed breed, with 40 days of life was seen with complaint of postprandial regurgitation that was repeated at each meal. On physical examination, the animal was below ideal weight, apathetic, with pale mucosa and bristly. It was suspected of megaesophagus, which was confirmed by contrasting thoracic lateral-lateral (LL) radiography, and the patient also had anterior partial esophageal dilation to the topographic image of the heart. The image was suggestive of persistence of the right aortic arch, and corrective surgery was indicated but it was not authorized by the tutors. Therefore, conservative dietary treatment was instituted. The animal remained stable for a period of one and a half years. After this period the patient returned with an aggravated condition of vomiting, anorexia and apathy. The same clinical condition was maintained in the chest X-ray. An esophageal flushing was indicated, which was not authorized by the tutors, being prescribed mucosal protector and antibiotic. The medication was maintained by the tutor and after 1 month of the initial care, the clinical condition worsened and the animal died. Case 2. A 6-month-old male Pinscher dog weighing 1 kg was seen with postprandial regurgitation complaint since the beginning of the weaning transition period. In the esophagography performed a compatible radiographic image was seen with a diverticulum of the cranial thoracic esophagus and congenital total megaesophagus. The treatment adopted was conservative. Twelve months after the initial care, the animal presented radiographically resolution of the diverticulum and megaesophagus and was in good health. Discussion: These cases report two rare conditions of esophageal diverticulum associated with megaesophagus in a feline and canine. In the case of the feline, it was possible to conclude that the formation of the diverticulum was secondary to not surgical resolution of the persistence of the right aortic arch, with consequent maintenance of the megaesophagus, since the diverticulum was not present in the first radiographic examination. In the second case, when the radiograph was taken, the animal already presented the cranial diverticulum to the total megaesophagus, which, together with the history of postprandial vomiting since the 45 days of life, suggested a delay in the maturation of the esophageal nervous system that caused the megaesophagus and impairment of normal peristalsis of the organ culminating in the formation of the diverticulum. Due to the rare condition in both species, there are no reports of predilection for race, age or sex of the animals affected by the diverticulum, whereas for the megaesophagus, when in the congenital form, it preferentially occurs in young dogs and cats [less than 2 years of age], at the time of transition from the liquid to the solid diet. Both reports were of young animals that had recently undergone a food transition, which would justify the appearance of the megaesophagus as the main cause of the esophageal diverticulum. The clinical signs presented by the animals were compatible with those reported in the literature. It is concluded that although the esophageal diverticulum occurred in both cases as a consequence of megaesophagus, the resolution of the underlying cause is decisive for the resolution of the clinical condition determining the patient’s prognosis. Keywords: regurgitation, food impacts, esophageal dysfunction.